2016
DOI: 10.1186/s12889-016-2830-6
|View full text |Cite
|
Sign up to set email alerts
|

A socio-ecological perspective of access to and acceptability of HIV/AIDS treatment and care services: a qualitative case study research

Abstract: BackgroundAccess to healthcare is an essential element of health development and a fundamental human right. While access to and acceptability of healthcare are complex concepts that interact with different socio-ecological factors (individual, community, institutional and policy), it is not known how these factors affect HIV care. This study investigated the impact of socio-ecological factors on access to and acceptability of HIV/AIDS treatment and care services (HATCS) in Wolaita Zone of Ethiopia.MethodQualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 42 publications
0
30
0
1
Order By: Relevance
“…A qualitative study conducted in the study area showed that the ways clients treated in the health facilities varied across health facilities and care providers and impacted the perceptions of clients towards responsiveness [60]. However, the findings also showed that all of the responsiveness domains had substantial proportions of their performance falling in the ‘good’ category, which meant that some expectations regarding the responsiveness domains were met.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study conducted in the study area showed that the ways clients treated in the health facilities varied across health facilities and care providers and impacted the perceptions of clients towards responsiveness [60]. However, the findings also showed that all of the responsiveness domains had substantial proportions of their performance falling in the ‘good’ category, which meant that some expectations regarding the responsiveness domains were met.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature suggests a mixed account of THPs’ knowledge and understanding of HIV/AIDS. Some studies have found that THPs consider HIV to be caused by a combination of physical, environmental and spiritual impurity [72,73]. THPs who held this perspective also said that they could treat HIV-related symptoms such as swollen lymph nodes, mouth and genital ulcers, weight loss and diarrhoea [72].…”
Section: Discussionmentioning
confidence: 99%
“…Levesque et al 12 mention that geographic availability impacts the affordability of health services. The impact of transportation cost on affordability is highlighted in studies from rural health, nutrition, maternal health, and public health disciplines 18–21 . Other indirect costs mentioned in the literature which relate to affordability include costs of insurance, time, taxes, and societal 19,22,23 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other indirect costs mentioned in the literature which relate to affordability include costs of insurance, time, taxes, and societal 19,22,23 . Additional studies describe the nonmonetary cost of stress that a financial transaction may incur 21,24–26 . Finally, Kurpas et al 27 describe a unique situation where one must essentially pay a price to make health care available.…”
Section: Literature Reviewmentioning
confidence: 99%